6. CLINICAL AND SUBCLINICAL CHARACTERISTICS OF PATIENTS WITH MODERATE AND SEVERE SEBORRHEIC DERMATITIS (Vietnam Journal of Community Medicine, 2024)
Objective: This study examined the clinical and subclinical characteristics of patients with moderate and severe seborrheic dermatitis (SD).Subjects and methods: A cross-sectional descriptive study of 62 adult patients with moderate and severe seborrheic dermatitis diagnosed at the National Hospital of Dermatology & Venereology from 08/2020 to 10/2021.Results: Seborrheic dermatitis occurred in 80.7% of males and 19.3% of females. The disease was common in patients with oily skin (69.3%). The age group of 20-49 year olds was mostly affected (80.7%). The average age of onset was 32.1 ± 12.6 years, and the average duration of disease was 3.9 ± 2.8 years. All patients with moderate and severe seborrheic dermatitis had basic lesions of erythema and scales. The main subjective symptoms were itching (100%) and burning sensation (87.1%). Lesions were scattered with indistinct or absent borders. The most affected sites were the facial area (75.8%) and scalp (71%). Seborrheic dermatitis was often accompanied by pityriasis versicolor (21%). The proportion of patients with moderate and severe seborrheic dermatitis had more than 20 Malassezia spores per field under KOH examination was 19.4%. The density of Malassezia in patients with severe SD was higher than in moderate SD but the difference was not statistical significance.Conclusion: Seborrheic dermatitis was commonly seen in male patients with oily skin. The most common skin lesions were erythema and scales, located on the scalp and face, with scattered distribution and indistinct borders. Malassezia density was higher in patients with severe SD than in moderate SD but not statisically significant.
Keywords: Seborrheic dermatitis, Malassezia.